Fundamentals of Islamic culture - Khan, Arif Ali (Discovery Pub. House, 2011)
Islam is the only religion, under the sun, which encompasses a whole of the life of man in this world and the world hereafter. Complete as per the natural needs of man, Islam was introduced in this world, over one thousand and four hundred years ago. Prophet Muhammad (Pbuh), who is the last and final Prophet in the line of about one lakh and twenty-four thousand prophets, and messengers, was endowed with the Holly Quran by Allah, the Almighty for benefit of mankind, in general. Prophet Muhammad (pbuh) was sent to this world as mercy for all the worlds - Rahmat-ul-lil-Aalamin.